2015
DOI: 10.1179/1074935714z.0000000016
|View full text |Cite
|
Sign up to set email alerts
|

Post-exercise hypotensive responses following an acute bout of aquatic and overground treadmill walking in people post-stroke: a pilot study

Abstract: Our results indicate people post-stroke can sustain sufficient walking intensities necessary to reduce BP following cardiovascular exercise. Also, these data suggest that ATW can elicit clinically meaningful reductions in DBP and night-time SBP. Thus, it is recommended for clinicians to consider ATW as a non-pharmaceutical means to regulate DBP and promote nighttime dipping of SBP in people post-stroke. However, caution is advised during the immediate hours after exercise, a period of possible BP inflation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…However, it must be acknowledged that the sample size was small. Even though this is a relatively common issue in studies including post-stroke patients ( Francica et al, 2015 ; Lai et al, 2015 ), caution is necessary for generalizing the present findings, since low statistical power is associated with an inflated type II error rate (i.e., accepting the null hypothesis when the null hypothesis is false). Also, due to the small sample, it was not possible to perform subgroup analyses according to sex, age, and class of anti-hypertensive drug.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…However, it must be acknowledged that the sample size was small. Even though this is a relatively common issue in studies including post-stroke patients ( Francica et al, 2015 ; Lai et al, 2015 ), caution is necessary for generalizing the present findings, since low statistical power is associated with an inflated type II error rate (i.e., accepting the null hypothesis when the null hypothesis is false). Also, due to the small sample, it was not possible to perform subgroup analyses according to sex, age, and class of anti-hypertensive drug.…”
Section: Discussionmentioning
confidence: 87%
“…The prolonged PEH occurred even though usual medication schedules were maintained, reinforcing the clinical impact of regular exercise for stroke patients. Lai et al (2015) investigated the effects of single bouts of aquatic and overground treadmill walking on the magnitude and duration of post-exercise ambulatory BP in post-stroke patients. Exercise bouts were performed for 15 min with an intensity corresponding to 70% VO 2 peak, and post-exercise BP was assessed for 9 h. In comparison to a non-exercise control session, reductions in DBP and SBP of 3%-6% were observed after aquatic but not overground treadmill walking.…”
Section: The 24-h Ambulatory Phasementioning
confidence: 99%
See 2 more Smart Citations
“…Cunha et al (2016) have suggested that older women excited a 45-min moderate-to-high intensity aquatic exercise, then resting for 21 h, showed an average reduction in SBP and diastolic blood pressure (DBP) of approximately five and one mmHg, respectively [ 16 ]. Lai et al (2015) have observed that SBP decreased by 7.3%, and DBP had no change 9 h after a 25-min aquatic walking exercise with 70% peak oxygen uptake (VO 2peak ) [ 17 ]. Rodriguez et al (2011) studied a 45-min aquatic brisk walking with 40% VO 2peak and found that the average SBP during 30-60 min after exercise and the average DBP during 45–60 min after exercise of untrained women decreased by 9.3% and 8.7%, respectively [ 18 ].…”
Section: Introductionmentioning
confidence: 99%